1995
DOI: 10.1210/jcem.80.7.7608268
|View full text |Cite
|
Sign up to set email alerts
|

Increased nocturnal melatonin secretion in male patients with hypogonadotropic hypogonadism and delayed puberty.

Abstract: Hypogonadotropic hypogonadism (IGD) and constitutional delayed puberty (DP) share a common pathophysiologic process, i.e. GnRH deficiency. Both conditions are heterogenous and exhibit different grades of GnRH deficiency. To discern whether these disorders of GnRH deficiency are associated with altered melatonin secretion profiles, we compared untreated young males IGD (n = 7) and DP (n = 7) to normal pubertal male controls (n = 6). Serum samples for melatonin, LH, and prolactin concentrations were obtained eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
3
11
0
Order By: Relevance
“…Furthermore, early morning measurement of elevated melatonin could mean an increase in total melatonin production; however, they also could mean a delay in the early morning fall in melatonin secretion. We, as others (2, 3), have been able to confirm the increased circulating melatonin in patients with IHH, and a tendency is also pointed to in primary hypogonadism, even using a single determination. Although subtle time-dependent changes in circadian melatonin secretion are best identified by sampling an individual subject at frequent intervals for a 24-h period, and interindividual variation in plasma melatonin levels is substantial, it has previously been shown that intraindividual variations tend to be relatively small (4-7).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, early morning measurement of elevated melatonin could mean an increase in total melatonin production; however, they also could mean a delay in the early morning fall in melatonin secretion. We, as others (2, 3), have been able to confirm the increased circulating melatonin in patients with IHH, and a tendency is also pointed to in primary hypogonadism, even using a single determination. Although subtle time-dependent changes in circadian melatonin secretion are best identified by sampling an individual subject at frequent intervals for a 24-h period, and interindividual variation in plasma melatonin levels is substantial, it has previously been shown that intraindividual variations tend to be relatively small (4-7).…”
supporting
confidence: 79%
“…While there are several publications showing that DEXA estimates are comparable to those derived from other techniques (2), there are others that show significant deviations (3)(4)(5)(6).…”
mentioning
confidence: 98%
“…N-acetyl-5-methoxytryptamine (melatonin; MLT) is secreted by the pineal gland in all vertebrates in a nyctohemeral rhythm with low val ues during the day and high values during the night [2] some seasonal breeders this indole derivative coordinates fertility phases to the seasonal light-dark changes of the environment [3] by downregulating the pulsatility of hy pothalamic GnRH secretion [4], In man the MLT blood levels decrease with age [5], with the strongest decline occurring around puberty. In precocious puberty, the MLT levels are lower than in age-matched controls [6] and in delayed puberty vice versa [7], making an involve ment of MLT in the control of the timing of puberty at least probable. An increasing number of papers [8][9][10][11][12][13][14] deal with the MLT excretion during childhood, but up to now we do not have a complete survey over the develop ment of MLT and 6-hydroxymelatonin sulfate (MLTS) excretion from prematurity to adolescence.…”
Section: Introductionmentioning
confidence: 98%
“…Conflicting data have appeared in the past decade, either indicating a relationship between pineal and gonadal functions, or negating it (1)(2)(3). Some previous studies have demonstrated that the function of the pineal gland is related to circulating levels of sex steroids, as plasma melatonin levels decrease with age (4,5), and may be increased in hypogonadism (6), reverting to previous levels when hypogonadism resolves (7,8); it is not known whether this was causative or coincidental. In contrast, other investigators have been unable to find a correlation between melatonin and gonadal status, either under physiological (pubertal development) or pathological conditions (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%